2021
DOI: 10.1111/1751-7915.13950
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous fungi are central components in microbial community structure in raw fermented sausages

Abstract: Summary Raw meat sausage represents a unique ecological niche rich in nutrients for microbial consumption, making it particularly vulnerable to microbial spoilage. Starter cultures are applied to improve product stability and safety as well as flavour characteristics. However, the influence of starter cultures on microbial community assembly and succession throughout the fermentation process is largely unknown. In particular the effect on the fungal community has not yet been explored. We evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…According to our current findings, P. pentosaceus CECT8330 has the effect of alleviating intestinal inflammation, so it should have the potential for applications in the treatment of PIBD. With the progress of technology, microorganisms are widely used in the field of food science (Chen et al, 2020 ; Zwirzitz et al, 2022 ). It was reported that microbial preparations including probiotics can be considered to help alleviate diseases through food supplements (Choi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to our current findings, P. pentosaceus CECT8330 has the effect of alleviating intestinal inflammation, so it should have the potential for applications in the treatment of PIBD. With the progress of technology, microorganisms are widely used in the field of food science (Chen et al, 2020 ; Zwirzitz et al, 2022 ). It was reported that microbial preparations including probiotics can be considered to help alleviate diseases through food supplements (Choi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoscape was used to compute the statistics and depict the generated network [49]. According to [14,50,51], keystone bacterial taxa were considered the nodes presenting the highest betweenness centrality and node degree. The network analysis was performed either using the whole dataset or restricted to the Italian samples.…”
Section: Amplicon Bioinformatics Data Analysismentioning
confidence: 99%
“…19−21 Recent microbial interactions based on correlation network analysis showed numerous significant correlations between CNS, LAB, and D. hansenii in fermented sausages. 22 Furthermore, targeted and nontargeted metabolomics analyses have revealed that synergistic effects of yeast−bacteria interactions led to further enrichment of amino acids derivatives in beer fermentation. 23 Thus, the interaction of D. hansenii with CNS and LAB may promote the accumulation of branched-chain esters and indole derivatives, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, building synthetic communities with metabolic interactions has been recognized as contributing to promising approaches to metabolite accumulation in addition to genetic engineering. Recent microbial interactions based on correlation network analysis showed numerous significant correlations between CNS, LAB, and D. hansenii in fermented sausages . Furthermore, targeted and nontargeted metabolomics analyses have revealed that synergistic effects of yeast–bacteria interactions led to further enrichment of amino acids derivatives in beer fermentation .…”
Section: Introductionmentioning
confidence: 99%